Patients with esophageal and stomach neoplasms perceptions about guidelines on preoperative received from nurse - Rodrigo Marques da Silva; Rhea Silvia de Ávila Soares; Letice Dalla Lana; Jucelaine Arend Birrer; Sadja Cristina Tassinari de Souza Mostardeiro (Universidade Federal de Santa Maria, 2011)
Objective: to understand patients with gastric and esophageal neoplasms perceptions about the preoperative guidelines to gastrectomy and esophagectomy surgeries. Method: This is a descriptive qualitative study, which the data was collected between November 2010 and January 2011 through a structured interview was used along with eight patients in the surgical clinic of the University Hospital of Santa Maria, Rio Grande do Sul. The information was interpreted through content analysis. Results: four categories emerged: feelings revealed by the patient in relation to orientation received; patient's perceptions towards the professional who conducted the orientation; Health guidance meaning for patients; and feelings experienced by patient about hospital discharge. Conclusions: patients received appropriate guidance about their surgeries and felt more calm and confident in relation the surgical procedure